Innovation in African food processing enterprises: Patterns and drivers - Tadesse, Getaw; Gachango, Florence (AKADEMIYA2063, 2022)
The need for industrial development in Africa has become more pressing than ever. Industrial development is key for structural transformation, which many African countries are struggling with, to sustain and deepen the observed solid economic growth of the last two decades (Newfarmer, Page, and Tarp 2019; Newman et al. 2016). It has also become a key strategy to tap into growing opportunities such as the high rates of urbanization, the growing labor force and its level of qualification, a high proportion of young people in the population structure, a growing domestic market, an increasing relative size of the middle class, the decrease in the severity of internal political confrontations and attenuation of intercountry armed conflicts, and the development of digital technologies (Ledeneva et al. 2020). Despite the wider narrative of “premature deindustrialization” associated with COVID-19, recent data show that deindustrialization is not the common experience for the majority of African countries and industrial sectors (Lopes and te Velde 2021). This creates another opportunity to renew efforts and refocus policy to promote industrialization.